Crimea at the Boundary of the 19th-20th Centuries: Historiography of Creation of National-Oriented Educational Literature for Elementary School, Traditional National Clothes, Formation and Development of Higher Education - Gemedzhi, Avva S.; Anafieva, Elzara R.; Yayayeva, Nazle M.; Yayayeva, Alime M.; Ablyamitova, Leylya H. (International Journal of Criminology and Sociology, 2022)
Significant changes taking place in the socio-economic and cultural life of Crimea, in connection with joining the Russian Federation, determine priorities in the field of national policy and education, the main of which are the formation of national and universal values, ensuring the educational needs of Crimeans, preserving cultural and historical traditions of education and training of the younger generation. The development of primary education in Crimea at the end of the 19th and beginning of the 20th centuries differs significantly from other regions due to the specificity of ethno-religious identities. The ethno-confessional situation in the territory of Crimea in the second half of the 19th - early 20th centuries was rather complicated. Multi-faceted study of the history of the Crimea show that Crimea remained multinational at any given period of history, such as the dominance of one of the ethnic groups of the peninsula, the various state systems.